Implementation of The Principal's Leadership Style Based on Qs. Ali Imran Verse 159 - Endang Zenal; An-An Andari; Andi Warsino; M Nasor (Jurnal Isema : Islamic Educational Management, 2024)
As time progressed, scientific leadership began to develop along with the growth of scientific management, which is better known as the science of leading. Leadership is a very important thing in school-based management. Principals as leaders have different leadership styles according to their character. Leadership characteristics contained in Qs. Ali Imran verse 159, namely: Meek and gentle. Being soft-hearted makes a leader more sensitive to what is happening around him. He is able to feel what other people feel. The research method used is a qualitative approach, namely field research. as a key instrument. In this research, the method used to collect data was observation, interviews, and documentation. Writing results: (1) a leader must be able to be a unifier in the midst of the diversity of Muslims and is also expected to be able to advance the lives of Muslims in the future; (2) There are many stories in the Qur'an that describe how a leader carries out his duties as a leader, it can help success educators while carrying out their duties; (3) Quality or good qualities in educational institutions must be built as early as possible which can be grown through the family environment. Reflections of a leader's good attitude include factors, one of which arises through religious norms.